2006
DOI: 10.1073/pnas.0604686103
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary constraint on Otx2 neuroectoderm enhancers-deep conservation from skate to mouse and unique divergence in teleost

Abstract: Otx2 is a paired type homeobox gene that plays essential roles in each step and site of head development in vertebrates. In the mouse, Otx2 expression in the anterior neuroectoderm is regulated primarily by two distinct enhancers: anterior neuroectoderm (AN) and forebrain/midbrain (FM) enhancers at 92 kb and 75 kb 5 of the Otx2 locus, respectively. The AN enhancer has activity in the entire anterior neuroectoderm at headfold and early somite stages, whereas the FM enhancer is subsequently active in the future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…1C, panels g to i). No sequences other than those of the BHP, Tcf/Lef, and X29 sites are scarcely conserved between mouse and zebrafish FM enhancers that have similar activities in forebrain and midbrain at somite stages (28,30).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1C, panels g to i). No sequences other than those of the BHP, Tcf/Lef, and X29 sites are scarcely conserved between mouse and zebrafish FM enhancers that have similar activities in forebrain and midbrain at somite stages (28,30).…”
Section: Resultsmentioning
confidence: 99%
“…Genetic analysis by enhancer mutants suggested that the FM enhancer, rather than the FM2 enhancer, plays major roles in the Otx2 expression in forebrain and midbrain. Moreover, the FM enhancer is conserved among vertebrate Otx2 orthologues, from skate to mammal and teleost orthologues, but the FM2 enhancer is unique to rodent Otx2 orthologues (28,30). The antagonistic interaction between Otx2 and Gbx has been suggested not only in mice, but also in chicks (19,24), Xenopus (61,62), and zebrafish (11,25).…”
mentioning
confidence: 99%
See 3 more Smart Citations